Communication from the executive of the Commonwealth, transmitting reports from Col. Charles Dimmock and Lt. Col. James H. Burton, in reference to the stores, machinery, &c., at Harper's Ferry - Dimmock, Charles, 1800-1863; Burton, James Henry, 1823-1894 (LLMC-digital (Series), 1861)
Governor John Letcher's transmittal letter and June 14, 1861 reports from Col. Charles Dimmock and Lt. Col. James H. Burton regarding the stores, machinery and other items captured at Harper's Ferry, for the new armory at Richmond.